Effect of different coating layer on the topography and optical properties of ZnO nanostructured - Mohamed, Ruziana; Mamat, M. H.; Malek, Mohd Firdaus; Ismail, Ahmad Syakirin; Mohd Yusoff, Marmeezee; Mohd Noor, Asiah; Khusaimi, Zuraida; Rusop, Mohamad (American Institute of Physics Inc., 2018)
Magnesium (Mg) and aluminum (Al) co-doped zinc oxide (MAZO) thin films were synthesized on glass substrate by sol-gel spin coating method. MAZO thin films were prepared at different coating layers range from 1 to 9. Atomic Force Microscopy (AFM) was used to investigate the topography of the thin films. According to the AFM results, Root Means Square (RMS) of MAZO thin films was increased from 0.747 to 6.545 nm, with increase of number coating layer from 1 to 9, respectively. The results shown the variation on structural and topography properties of MAZO seed film when it's deposited at different coating layers on glass substrate. The optical properties was analyzed using UV-Vis spectroscopy. The obtained results show that the transmittance spectra was increased as thin films coating layer increases.